Assessment of Intelligent Substation Based on an Improved Fuzzy Sets Method - Yuanchao Hu; Lina Yao; Jiangjun Ruan; Yunzhu An; Fan Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In the construction process of smart grid, an assessment on primary equipments intelligent transformation is an urgent content in the first batch of intelligent substation pilot project. Wide investigation of intelligent substation pilot projects was conducted seriously in several regional power grids in China. An mathematical model was established to assess the substation primary equipments intelligent transformation firstly; then, the Vague sets multi-objective decision theory was applied to the assessment model and the consistency inspection and weight solving method of Vague set theory was improved in this paper. Finally, a practical example was given to show the rationality and accuracy of the above improved method. The method can provide practical guidance to assess primary equipments intelligent transformation.